Painful conversations: Therapeutic chatbots and public capacities. Issue 1 (March 2020) - Yang, Misti
Today, conversations automated by algorithms and delivered via screens seek to heal wounds such as substance use disorders, wartime traumas, and a global pandemic. This article explores the relationship between painful conversations, automated discourse, and public action. By articulating what is lost when therapeutic conversations are had with artificial intelligence, I illustrate that painful, human conversations expand capacities—contextualizing, norm-building, and caring—that are necessary for the public reparation of wounds.